MGST1 is a redox-sensitive repressor of ferroptosis in pancreatic cancer cells. Issue 6 (17th June 2021) - Kuang, Feimei; Liu, Jiao; Xie, Yangchun; Tang, Daolin; Kang, Rui
Summary: Ferroptosis is a type of nonapoptotic cell death driven by lipid peroxidation. Here, we show a key role of MGST1 in inhibiting ferroptosis in cell cultures and mouse xenograft models. Ferroptosis activators induce MGST1 upregulation in human pancreatic ductal adenocarcinoma (PDAC) cell lines in an NFE2L2-dependent manner. The genetic depletion of MGST1 or NFE2L2 has a similar effect in promoting ferroptosis, whereas the re-expression of MGST1 restores the resistance of NFE2L2 -knockdown cells to ferroptosis. MGST1 inhibits ferroptotic cancer cell death partly by binding to ALOX5, resulting in reduced lipid peroxidation. The expression of MGST1 is positively correlated with NFE2L2 expression in pancreatic tumors, which is implicated in the poor prognosis of patients with PDAC. These findings not only provide a valuable insight into the defense mechanism against ferroptotic cell death, but also indicate that targeting the MGST1 redox-sensitive pathway may be a promising strategy for the treatment of PDAC. Graphical abstract: Highlights: NFE2L2 mediates MGST1 upregulation during ferroptosis MGST1 is a negative regulator of ferroptosis in vitro and in vivo MGST1 binding to ALOX5 limits lipid peroxidation during ferroptosis Increased MGST1 is associated with poor PDAC patient outcomes Abstract : Kuang et al. demonstrate that MGST1 plays a role in preventing ferroptosis by inhibiting ALOX5 activity and subsequent lipid peroxidation in human pancreatic cancer cells. These findings indicate that targeting the MGST1 pathway has the potential to modulate ferroptosis sensitivity in cancer therapy.